Iterative reconstruction improves detection of in-stent restenosis by high-pitch dual-source coronary CT angiography - Junjie Yang (Nature Portfolio, 2017)
Abstract Recent studies demonstrated that sinogram affirmed iterative reconstructions (SAFIRE) can produce higher-resolution images with greater robustness for the reduction of various imaging artefacts. Eighty-five patients were prospectively evaluated and underwent a high-pitch spiral acquisition CT scan. In-stent noise, signal-to-noise ratio(SNR), stent-lumen attenuation increase ratio (SAIR), and subjective image quality score were measured and compared between the SAFIRE and Filter back projection (FBP) reconstructions. Conventional coronary angiography served as the standard of reference. In 159 evaluated stents, SAFIRE was superior to FBP with regards to in-stent noise, SNR, SAIR, and image quality score. On per-stent analysis, SAFIRE vs. FBP reconstruction yielded 85% vs. 85%sensitivity, 89% vs. 78%specificity, 73% vs. 57%positive predictive value, 95% vs. 94%negative predictive value, and 0.87 vs. 0.82 area under curve, although these improvements did not reach statistical significance (P > 0.05). However, in the subgroup of small diameter stents (≤3 mm; n = 95), specificity(82% vs. 62%), positive predictive value(66% vs. 50%) and area under curve (0.81 vs. 0.70) improved significantly (P < 0.05) with SAFIRE. SAFIRE image reconstruction can thus improve the evaluation for ISR, especially in smaller stents.